Beyond CBD: Inhibitory effects of lesser studied phytocannabinoids on human voltage-gated sodium channels - Milligan, Carol J.; Anderson, Lyndsey L.; McGregor, Iain S.; Arnold, Jonathon C.; Petrou, Steven (Frontiers in Physiology, 2023)
Cannabis contains cannabidiol (CBD), the main non-psychoactive phytocannabinoid, but also many other phytocannabinoids that have therapeutic potential in the treatment of epilepsy. Indeed, the phytocannabinoids cannabigerolic acid (CBGA), cannabidivarinic acid (CBDVA), cannabichromenic acid (CBCA) and cannabichromene (CBC) have recently been shown to have anticonvulsant effects in a mouse model of Dravet syndrome (DS), an intractable form of epilepsy. Recent studies demonstrate that CBD inhibits voltage-gated sodium channel function, however, whether these other anticonvulsant phytocannabinoids affect these classic epilepsy drug-targets is unknown. Voltage-gated sodium (NaV) channels play a pivotal role in initiation and propagation of the neuronal action potential and NaV1.1, NaV1.2, NaV1.6 and NaV1.7 are associated with the intractable epilepsies, such as DS and Lennox-Gastaut syndrome (LGS). In this study, using automated-planar patch-clamp technology, we assessed the profile of the phytocannabinoids CBGA, CBDVA, cannabigerol (CBG), CBCA and CBC against these human voltage-gated sodium channels subtypes expressed in mammalian cells and compared their effects to CBD. CBD and CBGA inhibited peak current amplitude in the low micromolar range in a concentration-dependent manner, while CBG, CBCA and CBC revealed only modest inhibition for this subset of sodium channels. CBDVA inhibited NaV1.6 peak currents in the low micromolar range in a concentration-dependent fashion, while only exhibiting modest inhibitory effects on NaV1.1, NaV1.2 and NaV1.7 channels. CBD and CBGA non-selectively inhibited all channel subtypes examined, whereas CBDVA was selective for NaV1.6. These data advance our understanding of the molecular actions of lesser studied phytocannabinoids with channel proteins.